Hepatitis B Virus Virions Produced Under Nucleos(t)ide Analogue Treatment Are Mainly Not Infectious Because of Irreversible DNA Chain Termination. Issue 2 (19th August 2019) - Liu, Yongzhen; Liu, Hui; Hu, Zhanying; Ding, Yang; Pan, Xiao‐Ben; Zou, Jun; Xi, Jingyuan; Yu, Guangxin; Huang, Hongxin; Luo, Meng‐Ting; Guo, Fang; Liu, Shuang; et al.
Abstract : Nucleos(t)ide analogues (NAs) have been widely used for the treatment of chronic hepatitis B (CHB). Because viral DNA polymerase lacks proofreading function (3′ exonuclease activity), theoretically, the incorporated NAs would irreversibly terminate viral DNA synthesis. This study explored the natures of nascent hepatitis B virus (HBV) DNA and infectivity of progeny virions produced under NA treatment. HBV infectivity was determined by infection of HepG2‐NTCP cells and primary human hepatocytes (PHHs). Biochemical properties of HBV DNA in the progeny virions were investigated by qPCR, northern blotting, or Southern blotting hybridization, sucrose gradient centrifugation, and in vitro endogenous DNA polymerase assay. Progeny HBV virions produced under NA treatment were mainly not infectious to HepG2‐NTCP cells or PHHs. Biochemical analysis revealed that under NA treatment, HBV DNA in nucleaocapsids or virions were predominantly short minus‐strand DNA with irreversible termination. This finding was supported by the observation of first disappearance of relaxed circular DNA and then the proportional decline of HBV‐DNA levels corresponding to the regions of PreC/C, S, and X genes in serial sera of patients receiving NA treatment. Conclusion: HBV virions produced under NA treatment are predominantly replication deficient because the viral genomes are truncated and elongation of DNA chains is irreversibly terminated. Clinically, our results suggest that the viral loads of CHB patients under NA therapy vary with the different regions of genome being detected by qPCR assays. Our findings also imply that NA prevention of perinatal and sexual HBV transmission as well as infection of transplanted livers works not only by reducing viral loads, but also by producing noninfectious virions.